Invitro Evaluation of Fungicides and Botanicals against Fusarium oxysporum f.sp. cubense of Banana - Pant, B.; Manandhar, S.; Manandhar, C.; Baidhya, S. (Journal of the Plant Protection Society, 2020)
Abstract available with full text.